IMPLEMENTASI KETENTUAN PASAL 77 AYAT (3) PERATURAN DAERAH KABUPATEN LANDAK NOMOR 7 TAHUN 2010 TENTANG PENYELENGGARAAN ADMINISTRASI KEPENDUDUKAN KABUPATEN LANDAK - NIM. A1012191016, FRANSISKUS JERY (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac With the enactment of Law Number 23 of 2006 concerning population administration, it provides for the fulfillment of administrative rights such as public services and protection with respect to population documents without any discriminatory treatment. Civil registration is the right of every citizen in the sense of the right to obtain an authentic deed from a state official. Birth and death are important population events that must be recorded and become an important part of administration for the sake of good population administration. With the issuance of Law of the Republic of Indonesia Number 24 of 2013 concerning Amendments to Law of the Republic of Indonesia Number 23 of 2006 concerning Population Administration where in this case the reporting of death under the previous Law is the obligation of the family who died but in article 44 paragraph (1 ) The latest law states that this obligation is the responsibility of the RT where the citizen dies. As we know, not all RT heads are diligent or thorough in dealing with matters relating to population administration, maybe some are diligent, but most RT heads now have their own interests. As for this study, the author emphasizes that the type of research used is empirical legal research.So it can be concluded that the implementation of Article 77 Paragraph (3) of Landak Regency Regional Regulation Number 7 of 2010 concerning the Implementation of Population Administration of Landak Regency in Jelimpo District is currently not effective/maximum due to lack of socialization from agencies related to cultural factors, namely death events are considered normal and not needs to be reported to the authorized official and the essential Obstacles encountered in the Implementation of Article 77 Paragraph (3) Landak Regency Regional Regulation Number 7 of 2010 Concerning the Implementation of Population Administration for Landak Regency in Jelimpo District is implemented because some RT heads in Jelimpo District do not yet know the substance of Article 77 Paragraph (3) Landak Regency Regional Regulation Number 7 of 2010 concerning the Implementation of Population Administration for Landak Regency and the legal awareness of the community only increases when there is an interest in population events, namely the need for an inheritance certificate.Keywords: Population Administration, Death Reports, Regional Regulations AbstrakDengan berlakunya Undang-undang Nomor 23 Tahun 2006 tentang administrasi kependudukan memberikan pemenuhan hak-hak administratif seperti pelayanan publik serta perlindungan yang berkenaan dengan dokumen kependudukan tanpa adanya perlakuan yang diskriminatif. Pencatatan sipil merupakan hak dari setiap warga negara dalam arti hak memperoleh akta autentik dari pejabat negara. Kelahiran dan kematian merupakan peristiwa penting kependudukan yang harus di lakukan pendataan dan menjadi bagian penting dalam administrasi demi terselenggaranya administrasi kependudukan yang baik. Dengan terbitnya Undang-Undang RI Nomor 24 Tahun 2013 Tentang Perubahan Atas Undang-Undang RI Nomor 23 Tahun 2006 Tentang Administrasi Kependudukan dimana dalam hal ini pelaporan kematian yang di Undang- undang sebelumnya menjadi kewajiban dari pihak keluarga yang meninggal namun dalam pasl 44 ayat (1) Undang-undang terbaru disebutkan bahwa kewaajiban tersebut merupakan tanggung jawab RT dimana warga tersebut meninggal dunia. Seperti yang kita ketahui bahwa tidak semua ketua RT yang rajin atau teliti dalam mengurus hal-hal mengenai administrasi kependudukan, mungkin ada sebagian yang rajin, tapi kebanyakan ketua RT sekarang memiliki kepentingan masing-masing.Adapun dalam penelitian ini, Penulis menegaskan bahwa, jenis penelitian yang digunakan ialah penelitian hukum empiris.Maka disimpulkan bahwa Implementasi Pasal 77 Ayat (3) Peraturan Daerah Kabupaten Landak Nomor 7 Tahun 2010 Tentang Penyelenggaraan Administrasi Kependudukan Kabupaten Landak di Kecamatan Jelimpo saat ini belum efektif/maksimal karena kurangnya sosialisasi dari instansi terkait faktor budaya yaitu peristiwa kematian dianggap hal yang biasa dan tidak perlu dilaporkan ke pejabat yang berwenang dan Hambatan esensial yang ditemui dalam Implementasi Pasal 77 Ayat (3) Peraturan Daerah Kabupaten Landak Nomor 7 Tahun 2010 Tentang Penyelenggaraan Administrasi Kependudukan Kabupaten Landak di Kecamatan Jelimpo diterapkan karena sebagian ketua RT di Kecamatan Jelimpo belum mengetahui substansi Pasal 77 Ayat (3) Peraturan Daerah Kabupaten Landak Nomor 7 Tahun 2010 Tentang Penyelenggaraan Administrasi Kependudukan Kabupaten Landak dan kesadaran hukum masyarakat baru meningkat ketika ada kepentingan peristiwa kependudukan yaitu adanya keperluan akta waris.Kata Kunci : Administrasi kependudukan, Laporan Kematian, Pertur Daerah